Cruise passengers’ perceived value and willingness to recommend - David McA. Baker; Mark D. Fulford (Tourism & Management Studies)
This paper evaluates cruise passengers perceived value, satisfaction and willingness to recommend a cruise to someone. Passengers aboard an underway ship cruising the Caribbean were surveyed. Regression analyses revealed that, not surprisingly, perceived value and service quality aboard the ship are key determinants of willingness to recommend a cruise to someone else. More interestingly, however, the quality of the food aboard the ship and the degree to which cruisers found the destinations to be relaxing were also significant indicators. Implications for future research